Sub Tuum Praesidium: Marist brothers in Australia, 1872-2022 - Vodola, Max (The Australasian Catholic record, 2022)
Review(s) of: Sub Tuum Praesidium: Marist brothers in Australia, 1872-2022, by Julian Casey, John Luttrell, Peter Rodney and Neville Solomon (Mascot, NSW: Marist Brothers Australia, 2022), pp. 562, hardback, $45.00.